A delayed and severe presentation of coronectomy complication. (9th April 2019) - Pellatt, A.; Bhola, S.; Collin, J.; Cobb, A.
Abstract: Coronectomy involves removal of the crown of the tooth, while leaving the roots in situ . It is generally performed in the secondary care setting as an alternative to extraction of the entire tooth, when the mandibular third molar is in close proximity to the inferior alveolar nerve. Although many clinicians are aware of how to identify high‐risk mandibular third molars and the potential advantages of performing coronectomy on such teeth, they may not be familiar with the associated risks and potential complications associated with coronectomy. We report a severe, albeit rare, complication of coronectomy and discuss the risks associated with the technique.